Short-term symptom improvement in infants with suspected cow’s milk protein allergy using amino acid formula: a prospective cohort analysis - Wilsey, Michael J.; Baran, Jessica V.; Lamos, Luke; Beacker, Jesse; Florio, Jared; Oliveros, Lea; Sriaroon, Panida; Brown, Jerry M.; Vanderhoof, Jon A. (Frontiers in Nutrition, 2023)
Cow’s milk protein allergy (CMPA) occurs commonly in infants. While the long-term efficacy of amino acid formulas for managing CMPA is well established, there is limited data on the short-term symptom improvement of using amino acid formula (AAF). This study aimed to determine the short-term effects of managing suspected CMPA in infants aged six months and under using a commercial AAF. Healthcare providers who treated infants with suspected CMPA aged six months or younger (n=104) provided de-identified survey data in this prospective study. Healthcare providers scored symptoms for severity from 0 to 3 (none, low, moderate, severe) before using a commercial AAF at Visit 1 and at Visit 2 (3 to 6 weeks later). Gastrointestinal (94%), skin (87%), respiratory (86%), and uncategorized symptoms (89%) improved from AAF initiation, and these findings were consistent across different follow-up visit durations. This study is the most extensive prospective analysis conducted in the United States examining the short-term change in suspected CMPA symptoms using an AAF. These findings suggest that AAF may decrease the severity of suspected CMPA symptoms in infants six months or younger, often by the next follow-up visit. Further randomized controlled trials are required to confirm these initial findings.